Middle School General Music: The Best Part of Your Day - McAnally, Elizabeth Ann (Bloomsbury Publishing USA, 2016)
Create a viable, meaningful program that will motivate your students and have them participating with enthusiasm with Middle School General Music: The Best Part of Your Day.A welcome guidebook for music teachers trying to navigate the sometimes turbulent waters of middle school general music, it offers strategies and lessons that have been.